2018
DOI: 10.1002/jmri.26209
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic signature as a predictive factor for lymph node metastasis in early‐stage cervical cancer

Abstract: 3 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 27 publications
(46 reference statements)
1
68
1
Order By: Relevance
“…The radiomics signature developed in our study showed favorable discrimination for predicting LNM in the training and external validation sets, with AUCs of 0.859 and 0.833, respectively. The performance of our radiomics signature was comparable to previous studies (22,30). Kan et al (22) reported that the SVM-based radiomics signatures derived from T2W and cT1W images were associated with LNM, with an AUC of 0.753 in the primary cohort.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The radiomics signature developed in our study showed favorable discrimination for predicting LNM in the training and external validation sets, with AUCs of 0.859 and 0.833, respectively. The performance of our radiomics signature was comparable to previous studies (22,30). Kan et al (22) reported that the SVM-based radiomics signatures derived from T2W and cT1W images were associated with LNM, with an AUC of 0.753 in the primary cohort.…”
Section: Discussionsupporting
confidence: 82%
“…This strategy has shown a great potential for improved diagnostic and prognostic in a wide range of cancer types (16)(17)(18)(19). Few studies have suggested improvement in preoperative prediction of LNM by using different modalities-based radiomics analysis in cervical cancers (20)(21)(22)(23). However, these studies might suffer from relatively small sample sizes, analysis of single sequence or Abbreviations: LNM, lymph node metastasis; PLND, pelvic lymph node dissection; FIGO, International Federation of Gynecology and Obstetrics; MRI, magnetic resonance imaging; CSCC, cervical squamous cell cancer; DWI, diffusion-weighted imaging; FOV, field of view; ADC, apparent diffusion coefficient; ROI, region of interest; GLCM, gray-level co-occurrence matrix; GLRLM, gray-level run length matrix; GLSZM, gray-level size zone matrix; NGTDM, neighboring gray tone difference matrix; GLDM, gray-level dependence matrix; LoG, Laplacian of Gaussian; ICC, interclass correlation coefficient; MRMR, minimum redundancy maximum relevance; LASSO, least absolute shrinkage and selection operator; ROC, receiver operating characteristic; DCA, decision curve analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We defined the DL model-predicted LNM probability as the DL score. Owing to the inconsistency of previous research about the performance of MRI sequences, [13][14][15][16] we compared the DL model among 3 MRI sequences to find the optimal model for LNM prediction.…”
Section: Model Development and Visualizationmentioning
confidence: 99%
“…[10][11][12] Many attempts have been made to improve the performance of MRI in diagnosing LNM before surgery, for example, using radiomic features that extract the quantitative human-defined image features, such as shape, intensity, and texture features. [13][14][15][16] In previous research, the sensitivity of MR images to discriminate metastatic from nonmetastatic LN has shown improvement by using radiomic features. 13 However, radiomic features need time-consuming tumor delineation, and they might not be adaptive to specific clinical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignant tumors diagnosed among females worldwide ( 1 ). Furthermore, cervical cancer has a high incidence rate and exhibits the second highest mortality rate associated with cancer in women ( 2 , 3 ). Thus, cervical cancer seriously affects the health of women ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%